The effect of transcranial direct current stimulation combined with task-specific training on spatio-temporal gait parameters and functional mobility in individuals with stroke: a systematic review and meta-analysis - Miranda de Aquino Miranda, Jéssica; Sousa de Andrade, Pedro Henrique; Henrique, Maria Eduarda Salum Aveiro; Henrique de Souza Fonseca, Bruno; Bazan, Rodrigo [UNESP]; Sande de Souza, Luciane Aparecida Pascucci; José Luvizutto, Gustavo (Taylor & Francis, 2024)
Introduction: Transcranial direct current stimulation (tDCS) has a priming effect on post- stroke motor rehabilitation. Objective: We verified whether tDCS combined with task-specific training was superior to nonintervention, task-specific training, or simulated intervention in improving spatio-temporal gait parameters and functional mobility in stroke patients. Methods: We searched MEDLINE, EMBASE, CINAHL, Scopus, Cochrane Central, Web of Science, and LILACS for articles published until May 2024, using terms related to stroke, tDCS, and task-specific training. The risk of bias was assessed using the PEDro scale. The Grading of Recommendations, Assessment, Development, and Evaluation methodology was used to classify the certainty of the evidence for each outcome. Meta-analysis was performed using a random-effects model. Results: A total of 1,685 studies were identified, of which 18 were included in the qualitative analysis. Seven studies were included in the meta-analysis; all outcomes were classified as “very low quality.” Improvements in walking speed only were associated with tDCS combined with task-specific training (mean difference [MD], 0.06; 95% confidence interval [CI]: 0.04, 0.07; p < 0.001; I = 0%). There were no differences in other spatio-temporal gait parameters or functional mobility. Conclusion: This systematic review provides low-quality evidence that tDCS, in combination with task-specific training, increases speed in individuals after stroke. Both interventions, tDCS and task-specific training, are inexpensive and easy to implement; therefore, the mean estimate may be considered clinically worthwhile, although the CIs spans both clinically trivial and worthwhile effects. Registration: International Prospective Register of Systematic Reviews (PROSPERO; number CRD42023396021).
Keywords: locomotion training; spatiotemporal gait analysis; Stroke; task-specific training; transcranial direct current stimulation